Prediction of mental (psychological) pain based on psychological capital among people with grief experience because of Coronavirus: The mediating role of social support - Daliri, Roya; Fattahi andabil, Azam; Dokanehi Fard, Farideh (Applied Family Therapy Journal (AFTJ), 2021)
Aim: This study aimed to determine the prediction of mental (psychological) pain based on psychological capital among people with grief experience because of Coronavirus with the mediating role of perceived social support. Methods: The study design was descriptive correlational. The statistical population included people with the experience of grief of close family members (father, mother, child, sister, brother) caused by Coronavirus in 2021 in Tehran. According to the views of Hoit and Kramer (2004), 432 people were selected by purposive sampling, and they have completed the Mental Pain Scale by Orbach and Mikulincer (2003), the Luthans et al.'s (2007) Psychological Capital Questionnaire, and the Zimet et al.'s (1988) Perceived Social Support Scale. The collected data were analyzed using Pearson correlation coefficient and path analysis, and structural equations and using SPSS and Amoss software. Results: The outcomes of Pearson's correlation coefficients indicated that there is a positive and significant relationship between psychological capital (r = 0.38, p